Pengaruh Kompetensi Terhadap Kinerja Pegawai Dengan Lingkungan Kerja Sebagai Variabel Moderasi - Sowarno Suwarno; Irma Idayati; Hardi Mulyono; Windi Sundari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to find out how much influence competence has on employee performance with the work environment as a moderating variable at the Lubuklinggau City Youth and Sports Office. The method used in this study using a questionnaire and observation. The data analysis technique used is simple regression test, correlation coefficient, t test and moderation analysis. Testing the first hypothesis, namely the competency variable (X) on employee performance (Y) shows that t count produces a coefficient of 9.612. With a sample size of 39, it was found that df = 39 (39-2) at a significant level of 0.05, the critical t-table value was 1.687. With these results it can be said that competence has a significant influence on employee performance because t count (9.612) > t table (1.687). Testing the second hypothesis, namely the Competency variable (X) on employee performance (Y) with Work Environment (M) as a moderating variable shows that t count produces a coefficient of 4.791. With a sample size of 39, it was found that df = 39 (39-2) at a significant level of 0.05, the critical t-table value was 1.687. With these results it can be said that competence has a significant influence on employee performance with the work environment as a moderating variable because tcount (4.791) > t table (1.687). Based on the research results, it can be seen that to improve employee performance there must be competence so that it can control employee performance in completing its performance capabilities so that it is supported by an adequate work environment so it has an influence on employee performance.